2018
DOI: 10.3389/fphys.2018.00411
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of a Low Fat, Fructose-Rich Diet on Liver Metabolism, Insulin Signaling, and Oxidative Stress in Young and Adult Rats

Abstract: The increase in the use of refined food, which is rich in fructose, is of particular concern in children and adolescents, since the total caloric intake and the prevalence of metabolic syndrome are increasing continuously in these populations. Nevertheless, the effects of high fructose diet have been mostly investigated in adults, by focusing on the effect of a long-term fructose intake. Notably, some reports evidenced that even short-term fructose intake exerts detrimental effects on metabolism. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
7
18
1
2
Order By: Relevance
“…Investigations of the relationship between SSB intake and metabolic responses have also shown a statistically significant rise in blood pressure with fructose ingestion in healthy adults (Cai et al, 2018). Similar findings are also corroborated in fructose-fed animal studies (Nakagawa et al, 2006; Crescenzo et al, 2018). According to Johnson et al (2007), fructose-induced hyperuricemia may contribute to endothelial dysfunction and increased risk of hypertension.…”
Section: Hypertensionsupporting
confidence: 85%
“…Investigations of the relationship between SSB intake and metabolic responses have also shown a statistically significant rise in blood pressure with fructose ingestion in healthy adults (Cai et al, 2018). Similar findings are also corroborated in fructose-fed animal studies (Nakagawa et al, 2006; Crescenzo et al, 2018). According to Johnson et al (2007), fructose-induced hyperuricemia may contribute to endothelial dysfunction and increased risk of hypertension.…”
Section: Hypertensionsupporting
confidence: 85%
“…Intensive sugar consumption is increasingly measured as a key contributor to the worldwide epidemics of obesity and diets high in fructose have been shown to produce all of the key features of obesity and metabolic syndrome 23,24,25,26,27 , which is becoming a leading cause of death globally 28 . There is an obvious interplay of various factors in the onset and progression of obesity, however, metabolism being a crucial one plausibly due to sedentary or so-called modern lifestyles and thus has become a matter of immediate concern.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the oxidative stress response through the progression of the disease represents a challenge to merge features of NAFLD patients and mouse models and provide mechanistic insights and therapeutic opportunities (see Table 4). High-fructose diet [269] Mitochondrial ROS production Lipid peroxidation High-fat and high-fructose diet [270] Superoxide generation Mitochondrial NADPH oxidase 4 (NOX4) High-fat and high-sucrose diet [167] Lipid peroxidation Copper deficient diet [271] Obesity has been widely studied in recent decades, and a close connection between excessive body weight and ROS overproduction has been established [272]. A high-fat low-carbohydrate diet leads to impaired mitochondrial function and increased cellular oxidative damage [273].…”
Section: Dietary Patterns and Oxidative Stress In Nafldmentioning
confidence: 99%
“…Fructose and sucrose are also considered major mediators of NAFLD. A low-fat, fructose-rich diet results in marked oxidative stress levels in hepatocytes [269]. Moreover, García-Berumen et al demonstrated that the supplementation of a HF diet with fructose induces more severe hepatic damage as shown by the inhibition of state 3 and the impairment of Complex I activity, which subsequently promotes further mitochondrial ROS production [270].…”
Section: Dietary Patterns and Oxidative Stress In Nafldmentioning
confidence: 99%